Impact of PEDV infection on the biological characteristics of porcine intestinal exosomes - Wu, Junjie; Su, Langju; Ma, Guangmiao; Wang, Yichen; Luo, Yuhang; EI-Ashram, Saeed; Alajmi, Reem Atalla; Li, Zhili (Frontiers in Microbiology, 2024)
Porcine Epidemic Diarrhea (PED) is a highly contagious intestinal infection primarily affecting pigs. It is caused by the Porcine Epidemic Diarrhea Virus (PEDV).PEDV targets the villus tissue cells in the small intestine and mesenteric lymph nodes, resulting in shortened intestinal villi and, in extreme cases, causing necrosis of the intestinal lining. Moreover, PEDV infection can disrupt the balance of the intestinal microflora, leading to an overgrowth of harmful bacteria like Escherichia coli.Exosomes, tiny membrane vesicles ranging from 30 to 150 nanometers in size, contain a complex mixture of RNA and proteins. MicroRNA (miRNA) regulates various cell signaling, development, and disease progression processes. This study extracted exosomes from both groups and performed high-throughput miRNA sequencing and bioinformatics techniques to investigate differences in miRNA expression within exosomes isolated from PEDV-infected porcine small intestine tissue compared to healthy controls. Notably, two miRNA types displayed upregulation in infected exosomes, while 12 exhibited downregulation. These findings unveil abnormal miRNA regulation patterns in PEDV-infected intestinal exosomes, shedding light on the intricate interplay between PEDV and its host. This will enable further exploration of the relationship between these miRNA changes and signaling pathways, enlightening PEDV pathogenesis and potential therapeutic targets.